Gastro-intestinal involvement in systemic sclerosis - Saurabh Kedia; Anuj Chhaparia; Pramod Garg (Indian Journal of Rheumatology, 2017)
The gastrointestinal (GI) tract can be involved in up to 90% of patients with systemic sclerosis (SSc) and is the leading cause of morbidity and third most common cause of mortality in these patients. The GI involvement can occur in the absence of cutaneous manifestations in 10% of patients. Vasculopathy, cellular and humoral immunity, and diffuse fibrosis are the principal pathogenetic mechanisms in SSc and begin with autoantibody-mediated neuronal damage followed by muscular damage and fibrosis. This leads to progressive dysmotility of the entire GI tract from mouth to anus and is responsible for the clinical manifestations including gastroesophageal reflux disease and dysphagia due to esophageal involvement, gastroparesis, small intestinal bacterial overgrowth and chronic intestinal pseudo-obstruction, and constipation due to colonic and fecal incontinence due to anorectal involvement. The clinical features resulting from the involvement of these organs often overlap and multiple areas may be involved simultaneously. The treatment remains mostly symptomatic because effective disease-modifying therapies are lacking. These patients are at a risk of malnutrition and nutritional screening, and thus rehabilitation is very important. Refractory cases require nutritional support in the form of enteral nutrition and/or home parenteral nutrition. Future research is needed in the pathogenesis, development of biomarkers for early identification of GI involvement at the asymptomatic stage, and targeted disease-modifying therapies, which can alter/halt the disease progression.